A cold dark place eaudiobook - Olsen, Gregg (Emily Kenyon, 2020)
In a secluded farm house in the Pacific Northwest, a family has been slaughtered—and a teenage son has disappeared. Single mother and cop, Emily Kenyon spearheads a dark hunt for a killer. But Emily's teenage daughter Jenna is one step ahead of her. Then another family is butchered, and another. As Emily fits the puzzle pieces together, she makes a chilling discovery: the killer is coming after her and her daughter . . . Contains mature themes.